Pengaruh Debt To Equity Ratio, Return On Asset, Managerial Ownership, dan Sales Growth Terhadap Harga Saham - Mentari Pramudyani Elyanto; Menik Indrati (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to examine the influence of financial ratios on stock prices. The four selected financial ratios are Debt to Equity Ratio, Return on Assets, Managerial Ownership, and Sales Growth, which serve as the independent variables, while stock price functions as the dependent variable. The research focuses on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. A total of 144 samples were selected, consisting of 38 companies that met the established criteria. The results of this study indicate that only Return on Assets has a positive influence on stock prices, while the other independent variables are found to have no significant effect. These findings highlight the importance of profitability indicators in shaping market perception of a company's stock price, particularly within the food and beverage sub-sector. Therefore, this study can serve as a basis for companies and investors in making decisions to achieve their respective goals.